Tingkat Pengetahuan Perawat tentang Lima Momen Kebersihan Tangan - Nurul Safir; Mursal Mursal; Yudi Akbar; Abrar Abrar (Lentera : Jurnal Ilmiah Kesehatan dan Keperawatan, 2021)
Hand hygiene is one of the most important steps to prevent infection in health services and the nurses have a big role in preventing infection because they interact with patients for 24 hours. One of the factors that influence the application of the five moments of hand hygiene is the knowledge of nurses. The objective of this research was to determine the level of knowledge of nurses about five moments of hand hygiene. The research design was quantitative using descriptive method. The samples in this research were 35 nurses which were taken through total sampling technique. The measuring instrument was a questionnaire which consisted of 20 questions. The results of the research showed that the respondents who had knowledge of the five moments of hand hygiene in the high category was 16 respondents (45.7%), the range of age of 26-35 years was 16 respondents (45.7%), female sex was 27 respondents (77.1%), Associate degree of Nursing program was 30 respondents (85.7%) with a length of work for 1-5 years was 15 respondents (42.9%). It can be concluded that respondents who have knowledge about five moments of hand hygiene is in the high category. From the results of this research, it is expected that respondents can continue to improve their knowledge and compliance in carrying out the five moments of hand hygiene, especially in the second and fifth moments through training.